The technature / Muhammad Ammar Zamri ... [et al.] - Zamri, Muhammad Ammar; Ahmad Dali, Aiuni Anisah; Mohd Zamri, Muhammad Naufal Nabil (2024)
The Technature is a student hub designed for recreation and study outside of faculty spaces. This hub is closest to the lake at UiTM Seri Iskandar. So basically, a student hub might be a physical area on campus where students can access various services, resources, and activities. This is known as a student hub because it stands out as an eco-friendly space because it integrates technology with nature, featuring a solar power system that allows students to charge their devices and access free Wi-Fi. Student hubs centralise resources and support to make students' academic and social experiences more seamless and enriching. Since a mushroom is the subject matter of this design, the term "The Technature" refers to the concept of combining technology with nature.